Application Of Eco-Enzyme As An Explant Sterilization Material In Garlic Meristem Culture (Allium sativum L.) - Viza, Rivo Yulse; Darlis, Olivia (SINTA Journal (Science, Technology, and Agricultural), 2025)
Garlic (Allium sativum L.) is an important commodity with various benefits, both as food and medicine. One of the biggest challenges is the spread of diseases in garlic plants, which are often transmitted through bulbs or seeds used in planting. The initiation stage is the initial step of in vitro culture to obtain explants that are free of microbes and start early growth. Materials commonly used for sterilization of garlic explants are detergent, alcohol, and Clorox. Eco-enzyme is a result of the fermentation of fresh fruit waste containing bioactive compounds, such as organic acids and enzymes, which have the potential to be used as natural sterilization materials. The purpose of this study was to make eco-enzyme as a sterilization material for explants from fruit skin waste and to obtain the right explant sterilization method in in vitro culture propagation using eco-enzyme. A total of five sterilization methods have been tested in the Tissue Culture Laboratory of the Payakumbuh State Agricultural Polytechnic. The sterilization materials used were 70% alcohol, 10% Clorox, and eco-enzyme solution. The variables observed in this study were the percentage of contaminant types (fungi and bacteria), the time of contamination, and the percentage of living explants after 28 days of culture. The results showed that eco-enzyme A with a concentration of 100% has the ability as a surface sterilization material in garlic meristem culture, which produces a percentage of living explants of 100%.